Updates in essential tremor - Okelberry, Tyler; Lyons, Kelly E.; Pahwa, Rajesh (Parkinsonism & related disorders, 2024)
Essential tremor (ET) is one of the most common tremor disorders and can be disabling in its affect on daily activities. There have been major breakthroughs in the treatment of tremor and ET is the subject of important ongoing research. This review will present recent advancements in the epidemiology, genetics, pathophysiology, diagnosis, comorbidities, and imaging of ET. Current and future treatment options in the management of ET will also be reviewed. The need for continued innovation and scientific inquiry to address the unmet needs of persons of ET will be highlighted. •Essential tremor (ET) is a common condition, especially among people aged 65 years and older, and many ET cases in the general population are undiagnosed.•A single unifying model of pathophysiology leading to tremor generation is lacking and additional research is needed.•ET is associated with a wide range of important comorbidities, both neurologic and non-neurologic, which impact the lives of patients.•There is a substantial unmet need in the treatment of ET and several promising pharmacologic agents and devices are under investigation.